2016
DOI: 10.1089/jayao.2016.0009
|View full text |Cite
|
Sign up to set email alerts
|

Association ofBRCA1Mutations with Impaired Ovarian Reserve: Connection Between Infertility and Breast/Ovarian Cancer Risk

Abstract: Purpose: Mutations in the BRCA1/2 genes are associated with breast and ovarian cancer susceptibility. Recent studies have suggested that the BRCA mutation might be associated with occult primary ovarian insufficiency. To evaluate fertility, several studies have validated anti-Mullerian hormone (AMH) as a direct biomarker for ovarian aging and it is considered a quantitative marker of ovarian reserve. We hypothesize that BRCA1 gene mutations will be negatively associated with AMH levels. Methods: We evaluated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 28 publications
4
61
0
Order By: Relevance
“…(35) Another study examining 124 BRCA1 carriers and controls observed that BRCA1 carriers have increased odds of low AMH but only among women older than 35. (36)…”
Section: Discussionmentioning
confidence: 99%
“…(35) Another study examining 124 BRCA1 carriers and controls observed that BRCA1 carriers have increased odds of low AMH but only among women older than 35. (36)…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant evidence from small studies on women with BRCA1 mutations that these individuals have low ovarian reserve and poor response to fertility treatments. 7,117 There are few studies which fail to associate the link between BRCA1 and BRCA2 gene mutations, age of menopause, fertility problems, and parity. 118,119 Nonetheless, the converse, whether POI in itself carries a higher risk for breast, ovarian, or other forms of cancer is currently unknown.…”
Section: Accelerated Ovarian Aging and Adverse Health Outcomesmentioning
confidence: 99%
“…Another potential common mechanism between cancer and infertility is the presence of mutations in genes associated with DNA repair (e.g. BRCA) that may increase the risk of both conditions (Giordano et al, 2016;Johnson et al, 2017). In summary, our findings suggest an association between infertility and higher risk of cancer compared to a population deemed by claimsbased criteria to be non-infertile.…”
Section: Subset Analysesmentioning
confidence: 56%